"Virtual presence" in an Industrial Engineering course: how the Numerical Analysis and Advanced Calculus classes were developed during quarantine (AACINI - International Journal of Industrial Engineering, 2020)
Covid-19 radically changed everyone´s life, both in personal as labor aspects. The mandatory quarantine forced faculty to change their way of doing every task they did with students: teaching, communicating, assessing… Some of them, could overpass obstacles following what was planned for face-to-face classes, others not so well, and it is logical, since few was prepared for what had to be done.Students also had to meet the requirements to the fast pace of change in the way of learning. Some, with scarce technological resources could not link up the courses. Others were able to join them with some difficulty, many had no obstacles and were able to keep up.Numerical Analysis and Advanced Calculus, one of the subjects in the third year of Industrial Engineering at Facultad Regional San Nicolás (UTN), quickly adapted to the new modality of non-presence classes. The flipped classroom strategy continued, as in the previous years. Virtual presence in classes was made possible by Zoom, with a high attendance rate. The monitoring of student activities in Moodle was also important. Some Office 365 tools were also applied. Despite some difficulties appeared when assessing, the results in general were satisfactory, especially considering that desertion was not significant.The strategies and tools used and the results obtained during the first semester are shown here, and some proposals for the second semester, assuming that the "virtual presence" will continue.
Keywords: Virtual Presence; Forced Virtuality; Online Resources